Executive Committee Minutes 2017-02-09 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 1/26/17 – Approved. Chair Report. Faculty Eligible for Emeritus Status - Approved for Senate consent calendar. President Report. Statewide Senator Report. APARC Report. Resolution on the Investiture of President Sakaki referred back to T. Wandling. Provost Report. Next Steps for Office Hours policy – chair proposal sent back to FSAC. Posthumous Degree Request: Dylan Krings – Approved for Senate agenda. EPC Report. Senate agenda approved. FSAC Report. Associated Students Report. CFA Report. Chair Report continued.